COMPARISON OF MICRONIZED PROGESTERONE (CYCLOGEST PESSARY) AND PLACEBO IN PREVENTION OF PRE-TERM BIRTH IN TERTIARY CARE HOSPITAL - Afridi, Nighat; Fatima, Ambreen; Fareed, Amna; Khan, Saifullah; Khan, Shah Gul (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare efficacy of micronized per rectal progesterone (cyclogest pessary) and placebo inprevention of preterm birth in tertiary care hospital.Study Design: Randomized controlled trial (RCT).Place and Duration of Study: Study was conducted at department of gynecology and Obstetrics, CombinedMilitary Hospital Nowshera, Khyber Pakhtunkhwa, from Jan 2018 to Jun 2018.Methodology: A sample size of 140 patients was calculated using WHO calculator. Non probability consecutivesampling was used for recruitment of participants. Ethics approval and consent forms were taken. Women weredivided into two groups randomly. Group A was given micronized progesterone (cyclogest pessary) per rectalusage and group B was given placebo. Patients were followed for maternal and neonatal outcomes. Data wasanalyzed using SPSS version 23. Independent t-test was applied. p-value ≤0.05 was considered significant.Results: Total 140 patients were included in study. Mean age of women was 29.4 years ± 4.6SD. Patients in micronized progesterone (cyclogest pessary) was more effective in increasing birth weight (p=0.00), Apgar score maintenance at 1st (p=0.00) and 5th minute (p=0.000) and reduction in length of hospital stay (p=0.000) as compared to placebo. Patients were more satisfied with micronized progesterone (cyclogest pessary) per rectal as compared to placebo (p=0.00).Conclusion: Preterm birth is remained as significant issue in health care system of Pakistan. However, micronized progesterone (cyclogest pessary) per rectal usage had positive impact in improving maternal and neonatal health outcomes. Effective strategies for prevention of preterm birth in Pakistan are required.